2008
DOI: 10.4137/bbi.s313
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis in Diabetic Cardiomyopathy using Bioinformatics Approach

Abstract: Diabetic cardiomyopathy is a distinct clinical entity that produces asymptomatic heart failure in diabetic patients without evidence of coronary artery disease and hypertension. Abnormalities in diabetic cardiomyopathy include: myocardial hypertrophy, impairment of contractile proteins, accumulation of extracellular matrix proteins, formation of advanced glycation end products, and decreased left ventricular compliance. These abnormalities lead to the most common clinical presentation of diabetic cardiomyopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…25 Diabetic cardiomyopathy is the most dangerous complication facing patients with diabetes and is characterized by myocardial hypertrophy, impairment of contractile proteins, accumulation of ECM proteins, formation of advanced glycation end products and decreased left ventricular compliance. 26 It has been suggested that the accumulation of ECM proteins (in particular collagen fibres) may have an important role in the pathological changes associated with diabetic cardiomyopathy. 27 The present study showed that the classical features of diabetes (including disorder and collapse of diabetic cardiac muscle fibres, decreases in heart function and elevated blood glucose concentrations) were successfully induced in STZ-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…25 Diabetic cardiomyopathy is the most dangerous complication facing patients with diabetes and is characterized by myocardial hypertrophy, impairment of contractile proteins, accumulation of ECM proteins, formation of advanced glycation end products and decreased left ventricular compliance. 26 It has been suggested that the accumulation of ECM proteins (in particular collagen fibres) may have an important role in the pathological changes associated with diabetic cardiomyopathy. 27 The present study showed that the classical features of diabetes (including disorder and collapse of diabetic cardiac muscle fibres, decreases in heart function and elevated blood glucose concentrations) were successfully induced in STZ-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al [ 75 ], by simultaneously using real-time PCR and bioinformatics tools, identified genes associated with the cellular processes closely related to AD progression. Rao et al [ 76 ] used bioinformatics tools to identify almost 74 genes strongly involved in AD. The authors retrieved the encoded functional protein sequences in FASTA format from NCBI (National Center for Biotechnology Information) [ 61 ] and determined their role based on ClustalW multiple sequence alignments.…”
Section: Brief Overview Of Bioinformatics and Cheminformatics Tools Amentioning
confidence: 99%
“…In addition, they constructed a phylogenetic tree using the functional protein sequences. This study reported once more that the genetic components of AD are more important in comparison to environmental, metabolic and age related factors [ 76 ].…”
Section: Brief Overview Of Bioinformatics and Cheminformatics Tools Amentioning
confidence: 99%
“…Similarly aldose reductase and nitric oxide synthase were shown to be associated with diabetic retinopathy, suggesting they may do so by modulating aldose reductase and nitric oxide synthase [6]. Employing multiple sequence alignment using ClustalW to construct a phylogenetic tree, a causal relationship was suggested between altered calcium homeostasis and diabetic cardiomyopathy [7].…”
mentioning
confidence: 99%